The Constitutional Court in the Vortex of Resonance of Political Power - Rahmat Teguh Santoso Gobel; Ahmad, Ahmad; Yassine Chami (Universitas Islam Negeri Raden Intan Lampung, 2025)
The Constitutional Court of Indonesia stands as a fundamental pillar of constitutionalism and democracy remains vulnerable to the persistent. This article aims to critically examine how political influence infiltrates and affects the Court’s independence and institutional integrity, particularly through politicized judicial appointments and dismissals, personal relationships, and Utilizing a normative juridical approach, enriched by conceptual and case study analyses, most notably the controversial Decision No. 90/PUU-XXI/2023 and the dismissal of Justice Aswanto, this study identifies the concrete mechanisms of political interference and their implications for the Court’s legitimacy. The findings reveal a significant institutional shift: the Court is no longer functioning merely as a negative legislator, but exposing it further to political pressures. The study identifies eight specific factors of judicial non-independence in Decision No. 90/PUU-XXI/2023, signaling an acute integrity crisis. In response, the article proposes structural reforms, including amendments to the Constitutional Court Law, strengthening both internal and external oversight mechanisms, and reinforcing judicial self-restraint to curb judicial overreach. The conclusion emphasizes that institutional and ethical safeguards must be prioritized to protect the Court’s independence, uphold constitutional supremacy, and prevent democratic backsliding. Without comprehensive reform, the Court risks becoming an instrument of political power rather than a guardian of constitutional justice.